Consensus nomenclature rules for radiopharmaceutical chemistry — Setting the record straight - Coenen, Heinz H.; Gee, Antony D.; Adam, Michael; Antoni, Gunnar; Cutler, Cathy S.; Fujibayashi, Yasuhisa; Jeong, Jae Min; Mach, Robert H.; Mindt, Thomas L.; Pike, Victor W.; Windhorst, Albert D. (Nuclear medicine and biology, 2017)
Over recent years, within the community of radiopharmaceutical sciences, there has been an increased incidence of incorrect usage of established scientific terms and conventions, and even the emergence of ‘self-invented’ terms. In order to address these concerns, an international Working Group on ‘Nomenclature in Radiopharmaceutical Chemistry and related areas’ was established in 2015 to achieve clarification of terms and to generate consensus on the utilisation of a standardised nomenclature pertinent to the field. Upon open consultation, the following consensus guidelines were agreed, which aim to:•Provide a reference source for nomenclature good practice in the radiopharmaceutical sciences.•Clarify the use of terms and rules concerning exclusively radiopharmaceutical terminology, i.e. nuclear- and radiochemical terms, symbols and expressions.•Address gaps and inconsistencies in existing radiochemistry nomenclature rules.•Provide source literature for further harmonisation beyond our immediate peer group (publishers, editors, IUPAC, pharmacopoeias, etc.).